Use of Monte Carlo Simulation as a Tool for the Nondestructive Energy Dispersive X-ray Fluorescence (ED-XRF) Spectroscopy Analysis of Archaeological Copper-Based Artifacts from the Chalcolithic Site of Perdigões, Southern Portugal - Bottaini, C (2018)
This work is part of a broader research line that aims to develop and implement a nondestructive methodology for the chemical characterization of archaeological metals based on a protocol that combines energy dispersive X-ray fluorescence spectrometry (ED-XRF) with a Monte Carlo (MC) simulation algorithm. In this paper, the ED-XRF-MC protocol has been applied to estimate the chemical composition of a selected group of 26 copper-based artifacts and fragments recovered at Perdigo˜ es, one of the larger Chalcolithic sites of southwest Iberia. All the analyzed artifacts have a multilayered structure composed of the alloy substrate and of a superficial layer common in each metal buried for hundreds of years and consisting of the patina mixed with soil. Due to the difficulty in determining the quantitative composition of these alloys in the presence of this complex patina/encrustation layer, the spectrometric protocol applied in this paper allows to simulate and to determine the composition of the bulk alloy without any prior removal of the overlying corrosion patina layer and soil-derived crust, even in the presence of rough and irregular surfaces, thus preserving the physical integrity of the artifacts. The overall results obtained with the ED-XRF-MC protocol indicates that the artifacts from Perdigo˜es are almost pure coppers with a low amount of arsenic (<3.0 wt%) and reduced concentration of elements such as Pb, Bi, and Sb, in agreement with the third millennium metallurgy known in southwestern Iberia. Also based on previously theoretical– experimental studies, the data presented in this paper show how the applied analytical methodology can be a fast and completely nondestructive analytical tool reliable for routine and large-scale chemical analysis of archaeological metals, thus representing a major advance to be broadly applied within the field of cultural heritage studies.